If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(a + -4) = -2x + 1 Reorder the terms: 5 + -1(-4 + a) = -2x + 1 5 + (-4 * -1 + a * -1) = -2x + 1 5 + (4 + -1a) = -2x + 1 Combine like terms: 5 + 4 = 9 9 + -1a = -2x + 1 Reorder the terms: 9 + -1a = 1 + -2x Solving 9 + -1a = 1 + -2x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1a = 1 + -9 + -2x Combine like terms: 9 + -9 = 0 0 + -1a = 1 + -9 + -2x -1a = 1 + -9 + -2x Combine like terms: 1 + -9 = -8 -1a = -8 + -2x Divide each side by '-1'. a = 8 + 2x Simplifying a = 8 + 2x
| 8a-a=7a-6 | | 10(s-4)=-83 | | 2x+8+7+8x=4x+20+x+5 | | x^2+3x=304 | | 2(7x+2)+6=14x-10 | | -4[4-(3b+4)]=5-4(3b+8) | | 3(t-1)=9t | | -(c-20)=-2 | | x=6y-2x-9 | | x^4+3x^3+9x^2+27x=0 | | 7x+3-4x+15=6x+20-3x-2 | | x=gy-2x-9 | | U=2(8n+34)+7(n+1) | | 3x+4y+360=0 | | a^2+3a+3=7 | | 2x-(3+x)= | | 4y^2+4y-28=0 | | 5z-4=8z-4z | | 9x+11-6x-2=2x+4+x+5 | | 2x^2-4x+22=0 | | 7c+18=-5c+78 | | 9p^2+2=11 | | 7(3s+4)=154 | | 5y-7=9+4(y-2) | | 27(x^4)+9+x=0 | | 7(3s+4)=158 | | 4(2l+2)=16 | | n*5= | | n*-5= | | 3(a-7)=15 | | x^2+7+12=(p+[1])(p+2) | | 54-n=25 |